2022
DOI: 10.1186/s12875-022-01856-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lockdowns and distant learning on the health-related behaviours of school students in the United Arab Emirates

Abstract: Background The COVID-19 pandemic began to affect the world in early 2020. As a preventive measure, schools in the UAE adopted remote learning. This study aimed to assess the effects of the lockdown and remote learning on the health-related behaviours of school students in the UAE. Methods A cross-sectional study using an online survey comprising 33 questions related to physical activity, eating, sleeping and screen time was answered by the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The size of the gap is large and consistent across countries. This result is in line with the work of Sajwani et al ( 2022 ) reporting that in the UAE boys tend to do more moderate to vigorous physical activity than girls and suggesting that the pandemic could have exacerbated this gap. Moreover, in terms of household resources, girls were less likely to have a personal laptop (except in Uzbekistan) but, in Slovenia and Uzbekistan, they reported having a quiet space to study more frequently than boys.…”
Section: Resultssupporting
confidence: 91%
“…The size of the gap is large and consistent across countries. This result is in line with the work of Sajwani et al ( 2022 ) reporting that in the UAE boys tend to do more moderate to vigorous physical activity than girls and suggesting that the pandemic could have exacerbated this gap. Moreover, in terms of household resources, girls were less likely to have a personal laptop (except in Uzbekistan) but, in Slovenia and Uzbekistan, they reported having a quiet space to study more frequently than boys.…”
Section: Resultssupporting
confidence: 91%
“…This suggests that many individuals cannot maintain appropriate levels of physical activity during quarantine ( 6 9 ). Likewise, studies done in the UAE found similar results ( 11 13 ). It is essential to determine the extent of such patterns in the UAE to address them and prevent the deterioration of the population's health.…”
Section: Introductionsupporting
confidence: 67%
“…They reported that 10.3% of boys and 3.0% of girls were very obese between the ages of 15 to 18 years. However, another study found that the adverse effects of distance learning during the lockdown in the UAE included unhealthy food consumption and increased snacking, which might affect children’s weight [ 55 ]. Figure 3 and Figure 4 show the prevalence of overweight and obesity in children and adolescents aged between 5 to 19 years, according to the UAE country profile.…”
Section: Resultsmentioning
confidence: 99%